Searches for new phenomena in final states with taus using the ATLAS detector - Giuseppe Carratta (SciPost Physics Proceedings)
Many theories beyond the Standard Model predict new phenomena, such as leptoquarks, vector like leptons, $Z'$ and $W'$ bosons, supersymmetry, new scalars or heavy leptons, in final states with isolated, high-$p_{T}$ taus. Searches for new physics with such signatures, produced either resonantly or non-resonantly, are performed using the ATLAS experiment at the LHC. The most recent results at $\sqrt{s} =$ 13 TeV in proton-proton collision, are presented in this contribution.